(untitled) (The Himalayan Geographers, 2025)
Land is a gifted resource by nature. It is foundation of life and a major basis for agriculture. Land suitability refers to the degree to which a particular parcel of land is appropriate for human needs and purposes such as settlement, cultivation, or other usage. Generally, farming practices are often carried out spontaneously without identifying land suitability. The plantation of horticultural fruit species is also frequently done without determining scientific land suitability analysis. Among horticultural fruits, oranges (Citrus family) are a very popular product in Nepal as well as Syangja district, so, it is necessary to identify suitable land for their cultivation. This study aims to spatially identify the most suitable areas for orange production by integrating edaphic factor, accessibility, and socio-economic factors such as temperature, elevation, slope, soil texture, soil pH, soil depth, and proximity to water sources and roads. This study conducted a scientific Land Suitability Analysis (LSA) for orange farming in Syangja district using the Analytic Hierarchy Process (AHP) integrated with a Geographic Information System (GIS), based on field survey of 18 locations. The results of the final AHP weighted overlay analysis revealed a balanced distribution, with Highly Suitable land accounting for 25.44 percent (295.26 km²) and Moderately Suitable land for 24.79 percent (287.69 km²). These results confirm that slightly more than half of the district (50.23%) holds the required potential for viable orange production. Conversely, Marginally Suitable and Not Suitable areas comprise approximately 49.67 percent of the total landscape. The reliability of the AHP model was confirmed through field-based Ground Truthing, which indicated a high degree of accuracy with 12 specific locations falling within the highly suitable category and 6 falling within the moderately suitable category. Ultimately, these findings serve as a critical spatial planning tool for agricultural development policy, they direct strategic investment toward high potential zones of the study area, like Lalahi and Mayatari, while advising on risk mitigation and essential planning for moderately suitable regions like Changsing to facilitate the sustainable and profitable expansion.